2015
DOI: 10.1179/2049396714y.0000000094
|View full text |Cite
|
Sign up to set email alerts
|

Chronic low back pain among tobacco farmers in southern Brazil

Abstract: Background: Despite tobacco farming involving intensive manual labor, chronic low back pain (CLBP) prevalence and associated factors are unknown among this occupational group. Methods: This was a cross-sectional study conducted in southern Brazil. A random sample of tobacco farmers was interviewed. Socioeconomic and individual characteristics, occupational tasks, workloads, and comorbidities were investigated. Chronic low back pain prevalence was described in relation to independent variables, and associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 33 publications
4
38
0
19
Order By: Relevance
“…It is warned that cutting tobacco requires that the worker flex the spine to reach the foot of the plant, which, according to a study (21) , can cause problems in the spine, besides requiring a considerable physical effort, associated to the period of heat, greater perspiration and, consequently, increase in the absorption of nicotine. Researchers have identified that the harvesting of lower tobacco leaves is more likely to develop GTS by the above factors (10) .…”
Section: Discussionmentioning
confidence: 99%
“…It is warned that cutting tobacco requires that the worker flex the spine to reach the foot of the plant, which, according to a study (21) , can cause problems in the spine, besides requiring a considerable physical effort, associated to the period of heat, greater perspiration and, consequently, increase in the absorption of nicotine. Researchers have identified that the harvesting of lower tobacco leaves is more likely to develop GTS by the above factors (10) .…”
Section: Discussionmentioning
confidence: 99%
“…[11] These findings likely relate to many of the patients' occupations in manual labor and agricultural fields, which are well-established causes of MSK complaints. [16][17][18][19] Occupational customs in SV may impact hydration status. When asked, some patients reported that while doing agricultural work, it was very inconvenient to carry water and stay adequately hydrated.…”
Section: Discussionmentioning
confidence: 99%
“…The studies carried out by various authors [5,9,[13][14][15][16] revealed that low back pain was the most frequent type of pain that farmers reported, followed by neck, shoulder and upper back pain.…”
Section: Discussionmentioning
confidence: 99%
“…In their studies, scientists from Sweden [3], Nigeria [4], Brazil [5] and the USA [6][7][8][9][10][11] reported that low back pain and musculoskeletal disorder symptoms occurred among farmers.…”
Section: Introductionmentioning
confidence: 99%